Strategi Komunikasi Humas Polres Karanganyar dalam Kampanye Anti-Hoaks Pilkada 2024 Melalui Instagram - Destika Wahyu Pratiwi; Esfandani Peni Indreswari; Rahmat Wisudawanto (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study examines the communication strategy employed by the Public Relations Division of Karanganyar Police in delivering an anti-hoax campaign during the 2024 regional election stages through Instagram. The background of this research lies in the widespread dissemination of misinformation leading up to elections, which can disrupt social order. The purpose of this study is to analyze the effectiveness of digital communication strategies in increasing public literacy and maintaining the stability of public information. This research uses a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The results show that the communication strategy was implemented systematically through the four stages of the Cutlip, Center, and Broom model: fact-finding, planning, action and communication, and evaluation. Instagram was chosen for its ability to reach a younger audience and enable two-way interactions. Educational content presented in visual formats such as infographics and posters proved effective in delivering anti-hoax messages clearly and persuasively. The evaluation showed increased public engagement and a decline in the spread of hoaxes. This study suggests optimizing Instagram features and enhancing the creativity of the PR team to improve the effectiveness of future digital public communication.